Use of quantitative traits to assess aggressiveness of Phakopsora pachyrhizi isolates from Nigeria and the United States - Twizeyimana, M.; Ojiambo, P.S.; Bandyopadhyay, Ranajit; Hartman, G.L. (Scientific Societies, 2014)
Soybean rust, caused by Phakopsora pachyrhizi, is one of the most important foliar diseases of soybean worldwide. The soybean–P. pachyrhizi interaction is often complex due to genetic variability in host and pathogen genotypes. In a compatible reaction, soybean genotypes produce tan-colored lesions, whereas in an incompatible reaction soybean genotypes produce an immune response (complete resistance) or reddish-brown lesions (incomplete resistance). In this study, in total, 116 and 72 isolates of P. pachyrhizi from Nigeria and the United States, respectively, were compared based on six quantitative traits to assess their aggressiveness on two soybean genotypes. All isolates produced reddish-brown lesions on plant introduction (PI) 462312 and tan lesions on TGx 1485-1D. The number of days after inoculation to first appearance of lesions, uredinia, and sporulation, along with the number of lesions and sporulating uredinia per square centimeter of leaf tissue, and the number of uredinia per lesion, were significantly (P < 0.001) different between the two soybean genotypes for all isolates from each country. The number of days to first appearance of lesions, uredinia, and sporulation were greater on PI 462312 than on TGx 1485-1D for all the test isolates. Similarly, the number of lesions and sporulating uredinia per square centimeter, and the number of uredinia per lesion were lower on PI 462312 than on TGx 1485-1D. For both soybean genotypes, the number of sporulating uredinia per square centimeter significantly (P = 0.0001) increased with an increase in the number of lesions per square centimeter. Although the slope of the regression of sporulating uredinia on number of lesions was greater (P < 0.0001) when TGx 1485-1D was inoculated with Nigerian isolates compared with U.S. isolates, slopes of the regression lines did not differ significantly (P > 0.0675) when PI 46312 was inoculated with Nigerian or U.S. isolates. This is the first study that used a large number of isolates from two continents to assess aggressiveness of P. pachyrhizi using multiple traits in soybean genotypes with contrasting types of disease reaction.